A large new species of Passiflora, supersect. Laurifolia, ser. Quadrangulares (Passifloraceae) from the sub-Amazonian forests of Ecuador, with notes on its taxonomic alliance and distribution - Kuethe, J.r.; Montesinos, Kabir; Garzón-Suárez, Henry X.; Jost, Lou (Phytotaxa, 2023)
We here describe and illustrate Passiflora yolandae, a new species of Passiflora subgenus Passiflora, ser. Quadrangulares, from east-central Ecuador, and discuss its morphology, phenology, distribution, and relationships with other closely related species. This species is most notable for its unusual pendent inflorescence, with the flowers borne on relatively long and slender peduncles, with which it is readily different from its nearest related species. The flower buds, during the early stages of development, are nearly perfectly spherical. Literature studies have shown this plant to be found and collected during previous surveys; however, the sterile condition of those specimens never warranted it the recognition as a new species. We evaluate its conservation status as Endangered. An identification key to the species of Passiflora ser. Quadrangulares is provided.